The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1038/jp.2010.102
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic complications in the neonatal intensive care unit

Abstract: With the introduction of novel technologies and approaches in neonatal care and the lack of appropriately designed and well-executed randomized clinical trials to investigate the impact of these interventions, iatrogenic complications have been increasingly seen in the neonatal intensive care unit. In addition, increased awareness and the introduction of more appropriate quality control measures have resulted in higher levels of suspicion about and increased recognition of complications associated with deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 37 publications
1
22
1
2
Order By: Relevance
“…This agrees with a previous report that medication errors comprised 13% of total iatrogenic events (16), whereas other studies have reported that medication errors represented 68.5% of total errors (15). Another study found that half of the iatrogenic complications in the NICU were related to medication errors (9). Thus, we found wide variation between our own and other results.…”
Section: Discussioncontrasting
confidence: 54%
“…This agrees with a previous report that medication errors comprised 13% of total iatrogenic events (16), whereas other studies have reported that medication errors represented 68.5% of total errors (15). Another study found that half of the iatrogenic complications in the NICU were related to medication errors (9). Thus, we found wide variation between our own and other results.…”
Section: Discussioncontrasting
confidence: 54%
“…[2] For example, approximately half of the iatrogenic complications that occur in neonatal intensive-care settings are related to medication errors. [6] Broadly speaking, medication errors can be characterised as errors in the prescribing (including dose calculations), supply (dispensing) or administration of medicines, which include the elements of drug ordering, transcribing, communication, product labelling, packaging and nomenclature, compounding, dispensing, distribution, administering, monitoring, education and use. [1,3] Interpreting the literature is complicated by variations in terminology.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all diagnostic and therapeutic interventions and maneuvers can potentially promote ISIs. An IE may be defined as any event that occurs during hospitalization that compromises the safety of the patient, even if the patient is not harmed .…”
Section: Discussionmentioning
confidence: 99%
“…Almost all diagnostic and therapeutic interventions and maneuvers can potentially promote ISIs. An IE may be defined as any event that occurs during hospitalization that compromises the safety of the patient, even if the patient is not harmed (1,3,4). The more premature and smaller a neonate is, the more immature the organs and severe the developmental abnormalities are and the greater the number of general problems, infections, essential interventions, and procedures.…”
Section: Discussionmentioning
confidence: 99%